TANGGUNG JAWAB DIREKSI TERHADAP PEMEGANG SAHAM BERITIKAD BAIK ATAS PEMBELIAN KEMBALI SAHAM YANG BATAL KARENA HUKUM - MARHARA TUA MULYADI TAMBUNAN; RAMLI SIREGAR; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
The responsibility of director as the result of negligence in performing the work to the stakeholders is as full responsibility. Regarding the responsibility, the director must return all losses suffered by stakeholders since repurchase of the shares is against the prevailed law in company. The thesis studied some problems about the responsibility of director and stakeholders in running company, how is legal clause governing repurchase of share by the company, and how is the responsibility of director to stakeholders with good-will on repurchase of postponed shares by legal according to Act No 40 of 2007 concerning with limited company. The method of research used was normative research method by collecting data from library and secondary data from books, articles, newspapers and magazines as well as laws. The results of research concluded that the responsibility of director is fully to implement and run the company, whereas the responsibility of stakeholder is limited to and focus on the principle of separate entity and corporate entity producing limited stakeholders. Legal clause governing repurchase of shares by the company is UUPT which allows the company to repurchase its shares and can be seen in article 37, article 38, article 39 and article 40 UUPT. Kata Kunci: Tanggung Jawab Direksi, Pemegang Saham Beritikad Baik, Pembelian Kembali Saham.